Report of Meeting. The Twenty-first Katowice–Debrecen Winter Seminar on Functional Equations and Inequalities Brenna (Poland), February 2-5, 2022 - AMSil, Redakcja (Annales Mathematicae Silesianae, 2022)
Report of Meeting. The Twenty-first Katowice–Debrecen Winter Seminar on Functional Equations and Inequalities Brenna (Poland), February 2-5, 2022.